IDENTIFIKASI BAKAT OLAHRAGA DENGAN METODE SPORT SEARCH PADA SISWA-SISWI KELAS V DAN VI SEKOLAH DASAR NEGERI SE-KECAMATAN AIKMEL TAHUN 2020 - Putri, Kireina Hana; Syarifoedin, Elya Wibawa (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
This research is motivated by many students who have extraordinary potential and talents, naturally, coaching has not been optimally touched. Limited access to information, costs, and attention so that this potential is simply eroded by increasing age. The purpose of this research is to want to know the potential of sports talents possessed by students of Public Elementary Schools in Aikmel District in 2020. The research method used is descriptive quantitative. The sample of this research was 64 students of 5 public elementary schools in Aikmel District using random sampling technique. The test instrument measures height, sitting height, weighing, throwing a tennis ball, jumping upright, running agility, running 40 meters, running multi-stages. The data analysis technique was done by using sports search software. The results showed that the sports search data ranking for the percentage of the first rank in the diving sport was 43 students with a percentage of 67.2%, in the second rank Table Tennis was 9 students with a percentage of 14%, in the third rank Athletics high jump was 5. students with a percentage of 7.8%, in rank IV cricket as many as 4 students with a percentage of 4.7%, in rank V Gymnastics as many as 3 people with a percentage of 4.7%. Based on the results of the research above, it can be concluded that 64 students from 5 State SDs in Aikmel District, so from all SD Negeri students in Aikmel District who dominate the sports talents of Public Elementary School students in Aikmel District in 2020, namely the diving sport.